The carbonyl-lock mechanism underlying non-aromatic fluorescence in biological matter - Díaz Mirón, Gonzalo (2023)
Challenging the basis of our chemical intuition, recent experimental evidencereveals the presence of a new type of intrinsic ﬂuorescence in biomoleculesthat exists even in the absence of aromatic or electronically conjugated che-mical compounds. The origin of this phenomenon has remained elusive so far.In the present study, we identify a mechanism underlying this new type ofﬂuorescence in different biological aggregates. By employing non-adiabatic abinitio molecular dynamics simulations combined with a data-driven approach,we characterize the typical ultrafast non-radiative relaxation pathways activein non-ﬂuorescent peptides. We show that the key vibrational mode for thenon-radiative decay towards the ground state is the carbonyl elongation. Non-aromatic ﬂuorescence appears to emerge from blocking this mode with stronglocal interactions such as hydrogen bonds. While we cannot rule out theexistence of alternative non-aromatic ﬂuorescence mechanisms in other sys-tems, we demonstrate that this carbonyl-lock mechanism for trapping theexcited state leads to the ﬂuorescence yield increase observed experimentally,and set the stage for design principles to realize novel non-invasive bio-compatible probes with applications in bioimaging, sensing, andbiophotonics.